APLIKASI METODE SINGULAR SPECTRUM ANALYSIS (SSA) PADA PERAMALAN CURAH HUJAN DI PROVINSI GORONTALO - Eka Purnama (Department of Mathematics, Universitas Negeri Gorontalo, 2022)
This paper aims to study the forecasting model of rainfall in Gorontalo Province and forecast it for 2022-2023. Usually, rainfall data is seasonal. In this study, we used Singular Spectrum Analysis (SSA) with the Linear Recurrent Formula (LRF) method. The result showed that the models of rainfall forecasting in Gorontalo using SSA with windows lengthL=36 obtained MAPE of forecasting in out-sample was 0,029 or 2,9 %. So that SSA was very accurate in forecasting rainfall in Gorontalo Province in 2022-2023. The forecasting result showed that rainfall was relatively high generally. So, it is necessary for the government to take policies to avoid the negative impact that can be caused.